Buddhist Values and Actions Towards Peacd and Environment Protection. A Sociological Perspective - Díaz, José A. Rodríguez (The Journal of International Association of Buddhist Universities (JIABU), 2018)
Peace and Environmental Protection are two key issues and central avenues of Buddhist global social and political action contributing to a better future world. This paper looks into the social values and actions of Buddhist people of some Asian countries regarding war-peace and environmental protection issues. I try to place the analysis within the Buddhist cosmovision (meanings and practices) regarding the self (or no-self) and especially regarding the other beings (interconnection, dependent origination). Buddhist orientations and practices such as Loving Kindness of the Four Immeasurable are also part of such cosmovision. I use loving-kindness (love and orientation towards others) as a larger cultural and social identity frame acting as an umbrella under which views and practices towards peace and environment emerge.